Smoking, Alcohol, Diabetes, Obesity, Socioeconomic Status, and the Risk of Colorectal Cancer in a Population-Based Case–Control Study - Boyle, T.; Fritschi, Lin; Tabatabaei, S.; Ringwald, K.; Heyworth, J. (Kluwer Academic Publishers, 2014)
Purpose: Although previous research has identified factors that may determine willingness to participate in research, relatively few studies have attempted to quantify the impact non-participation may have on exposure–disease associations. The aims of this study were to (a) investigate the associations between smoking, alcohol, diabetes, obesity, and socioeconomic status and the risk of colorectal cancer in a case–control study (59.7 and 47.2 % response fractions among cases and controls, respectively); and (b) perform sensitivity analyses to examine the possible influence of non-participation. Methods: Logistic regression was used to estimate the exposure–disease associations. We then investigated the associations between various demographic and health factors and the likelihood that an individual would participate in the case–control study and then performed two sensitivity analyses (sampling weights and multiple imputation) to examine whether non-participation bias may have influenced the exposure–disease associations. Results: The exposures alcohol, smoking, and diabetes were associated with an increased risk of colorectal cancer. We found some differences between cases and controls when examining the factors associated with the participation in the study, and in the sensitivity analyses, the exposure–disease associations were slightly attenuated when compared with those from the original analysis. Conclusion: Non-participation may have biased the risk estimates away from the null, but generally not enough to change the conclusions of the study.